(untitled) (Cambridge,New York, 2002)
This study introduces several recent innovations in latent class analysis to a wider audience of researchers. Many of the world's leading innovators in the field of latent class analysis have contributed essays to the volume, each presenting a key innovation to the basic LCM and illustrating how it can prove useful in situations typically encountered in actual research
Keywords: Latent structure analysis,Latent variables,Toán học thống kê,Biến ẩn